Grader learning effect and reproducibility of doppler spectral-domain optical coherence tomography derived retinal blood flow measurements - Rose, Kalpana; Jong, Monica; Yusof, Firdaus; Tayyari, Faryan; Tan, Ou; Huang, David; Sadda, Srinivas R; Flanagan, John G; Hudson, Christopher (John Wiley & Sons Ltd, 2014)
PURPOSE: To investigate grader learning effect and to quantify intergrader reproducibility of Doppler Spectral-Domain Optical Coherence Tomography (SD-OCT) derived retinal blood flow measurements. METHODS: